Study of the behaviour of the male and female oriental pied hornbills in the wild and in captivity during the breeding cycle. - Tjai Madeline. (2011)
During the Oriental Pied hornbill(OPH) breeding cycle, the female seals herself inside the nest for the entire nesting cycle, emerging only when her chicks are ready to fledge. The use of a 24hour CCTV surveillance system and temperature and humidity sensors, has made it possible to study and observe detailed behaviour of the Oriental Pied Hornbill during breeding cycle. In this study, direct observations to study behaviour of 2 pairs of Oriental Pied Hornbills, one captive pair at Jurong Bird Park and one wild pair at Palau Ubin were made. Temperatures and humidity levels were also used to record daily readings on 10min intervals providing insights on how environmental factors can affect OPH behaviour. The behaviour of the female Oriental Pied Hornbill greatly affects the hatching of the eggs and growth of the chicks. Comparisons of the types of food and frequency of feedings were also made for both pairs. This year was an unsuccessful year for the wild pair at Palau ubin due to the death of all the chicks. The captive pair at Jurong Bird Park had only managed to breed one chick despite laying 3 eggs altogether.